Assistive knee joint device for overweight person - Saleem, Azizullah (Kulliyyah of Engineering, Internationai Islamic University Malaysia, 2015)
This research presents a light weight assistive knee joint device for overweight persons. Overweight persons (BMI between 25-30 kg/m2) experience 2.9-4.7 times the bodyweight load at the knee joint during walking, as such their knee joints are exposed to the danger of crushing. To lead healthy normal life, overweight persons need to reduce body weight. Overweight people need to walk for a longer duration to have more metabolic activity so that more calories are burnt to reduce body weight. So far such devices have not been researched to help the overweight people reduce their body weight through walking for a longer duration without damaging their knee joints. Research has shown that two main muscles which are the Vastii medial muscle and Gastrocnemius muscle contribute the most to the knee joint during walking. Thus overweight peoples require knee support systems which will reduce stresses at the knee joints as well as minimize muscle activations around the knee joint to help them walk for a longer time safely. A light weight exoskeleton consisting of a compression spring, a standard universal joint, a screw jack based mechanism, and straps for attaching the device with the thigh and the leg is developed to reduce the load at the knee joint. The screw jack helps adjust the initial deflection of the compression spring to support a portion of the body weight and then transfers this weight to the leg. The research investigated the effectiveness of this exoskeleton compared to the knee band by conducting experiment with a compression spring set to 2.5 cm deflection. The results show that both the knee band and exoskeleton reduces the Gastrocnemius muscle activity significantly. The average muscle reduction for the knee band was 66.32 % while for the exoskeleton prototype it was 63.32% with respect to the maximum muscle excitation during reference phase. The knee band reduces Gastrocnemius muscle activity more than the proposed exoskeleton. Due to the compression of the spring, 16.8 kg force load has been reduced at the knee joint. Though the muscle activation reduction is higher when using knee band, the range of load reduction cannot be adjusted as in the developed assistive knee joint since it is unable to sustain any compressive load. The higher muscle activation of the assistive device may be due to the straps arrangements and shape. It is expected that further research would help to improve the performance of this device.